Exploring challenges and facilitators to E-learning based Education of nursing students during Covid-19 pandemic: a qualitative study - Fereshteh Araghian Mojarad; Ali Hesamzadeh; Tahereh Yaghoubi (BMC, 2023)
Abstract Background During the COVID-19 pandemic, there was a shift to e-learning and online education in educational and learning processes. Research has shown that nursing students who are satisfied with e-learning tend to have better learning outcomes. Therefore, this qualitative study aimed to explore the challenges and facilitators of e-learning for nursing students during the pandemic. Methods This qualitative study utilized a content analysis approach. Sixteen participants with nursing education experience were purposively selected and interviewed using a semi-structured format. The data collected were analyzed using the conventional qualitative content analysis approach. Results Through data analysis, two main categories were identified: e-learning challenges and facilitators. The e-learning challenges included subcategories such as inexperienced teachers, ineffective learning, academic cheating, system problems, and inappropriate evaluation. The facilitators included subcategories such as improving education, and promoting online exams. Conclusions While e-learning was adopted as a substitute for in-person education during the COVID-19 pandemic, its implementation involves both challenges and facilitators. By addressing the challenges and optimizing the facilitators of e-learning, nursing schools can successfully adapt to this new mode of education in the post-pandemic era and provide high-quality education to their students.